A Biodegradable Multifunctional Film as a Tissue Adhesive for Instant Hemostasis and Wound Closure. Issue 9 (1st April 2022) - Huang, Wen‐Can; He, Yongjun; Wang, Wei; Mao, Xiangzhao
Abstract: Here, a multifunctional film (MFF) as an alternative tissue adhesive in the form of an interpenetrating network consisting of self‐crosslinked aldehyde‐functionalized chitosan (AC) and crosslinked poly(acrylic acid) (PAA) further coordinated with Ag + is reported. The MFF combines enhanced toughness and stretchability, which is attributed to the synergistic effects of the double‐network design. Covalent crosslinking maintains the overall integrity of the MFF matrix, while noncovalent crosslinking dissipates energy under deformation. Upon contact, the MFF quickly dries the tissue surface followed by instant physical crosslinking to the tissue. Subsequent covalent crosslinking between the aldehyde groups of the MFF and the primary amine groups on the surface of the tissue further stabilizes the adhesion. Meanwhile, Ag + provides strong antibacterial properties to the MFF. Notably, in vivo studies demonstrate that the MFF allows facile and tough attachment to the wet and dynamic surface of rabbit liver and presents superior hemostasis and sealing properties. Furthermore, the MFF can be safely degraded without causing abnormal defects in vivo. The outstanding physicochemical properties of the MFF can potentially be a good alternative to existing sutures or staples and has potential for use in clinical practice. Abstract : A multifunctional film (MFF) as an alternative tissue adhesive in the form of an interpenetrating network is presented. The MFF combines outstanding physical and antibacterial properties, allows facile and tough attachment to the wet and dynamic tissues and exhibits superior hemostasis and sealing properties.